SPATIAL STATISTICAL METHODS IN THE ANALYSIS OF PUBLIC HEALTH DATA - Shyti, Bederiana; Fetahu, Elona; Fetahu, Elvira (European Scientific Journal, ESJ, 2015)
Various studies claim that cancer is likely to be caused by the diverse environmental pollutants; lifestyle, i.e., poor diet, smoking, alcohol, stress, sun exposure, lack of physical activity, non-healthy weight; genetic inheritance; some kind of infections, etc. In most cases, around 90-95% of cancers are due to lifestyle and ecological factors that influence the living organisms. This implies that people affected by cancer most probably are clustered around the most polluted regions, meaning that the geographical location has an effect in the chances of contracting the disease. We use spatial statistical methods to support this and to point out the contrasts in rates that come out from different geographical distributions of the population. After the heart disease, cancer is the second cause of the worldwide deaths, in spite of the intensive research done in the last years. Based on the information on the causes of deaths by group diseases, provided by the Albanian Institute of Statistics INSTAT for the last two decades, this fact is also true in the case of Albania, where on the first place we have the circulatory system diseases with an average of 242 deaths per 100.000 inhabitants a year, followed by an average of 78 deaths per 100.000 inhabitants a year caused by neoplasm. In this study we take into consideration some specific geographical areas and see how the critical points do influence in the higher chance of being affected by cancer. We use correlation to show the relation between number of sick people and air pollution rates.